Association Between Body Mass Index and Precocious Puberty Among Girls in Sulaymaniyah: A Retrospective Cross Sectional Study - Jalal, Ako Kareem; Saeed, Heersh HMH Raof (Journal of Sulaimani Medical College, 2025)
Background: Precocious puberty, characterized by the early onset of secondary sexual characteristics before age 8 or menarche before 10, is a growing global health concern. There is no evidence about the correlation between childhood obesity and precocious puberty in the Kurdistan Region of Iraq. This paper explores the correlation between early pubertal indicators and body mass index (BMI) in girls living in Sulaymaniyah. Methods: A cross-sectional study was employed from September 2024 to June 2025 at Dr. Jamal Ahmad Rashid Pediatric Hospital, involving 93 females aged 4–10 years with complete medical records. Participants were assessed for clinical signs of puberty, BMI, bone age, and hormonal levels. Exclusion criteria included non-pubertal conditions, chronic illnesses, and medication-induced cases. Results: A significant portion of the participants was overweight (26.9%) or obese (33.3%). Dieting was highly correlated with overweight and obesity and physical inactivity was significantly prevalent among overweight and obese girls. Basal LH (p = 0.015), stimulated LH (p = 0.013) estradiol and increased bone age advancement (p =0.004) were significantly associated with elevated BMI categories. Basal LH, stimulated LH (p = 0.008) and estradiol (p = 0.005) in obese participants were significantly more elevated when compared to normal weight peers. A family history of obesity was closely related to higher BMI Conclusion: High BMI has a strong association with hormone and skeletal markers of precocious puberty among this cohort, and obesity is a key modifiable risk factor of early pubertal development in Sulaymaniyah
Keywords: Precocious puberty; Obesity; BMI; Bone age